Peranan Keteladanan Guru Dalam Penanaman Akhlak Siswa(StudiKasus di SMP Muhammadiyah10 SurakartaTahun2015/2016) - Nipaisah Sani, Miss (2016)
The teacher is an educator who greatly influenced the knowledge and character of students. Being a teacher should have a good model to be emulated protégé. Good example to be applied by teachers can be speech, manners as well as examples of good behavior in everyday life. Teachers who give good example in terms of character and knowledge to the students greatly affects the character of students both at school and in society. If the character of students increases and is well organized then it will give a lot of influence even increase good behavior in the school, family and community environment. Formulation of the research problem is how the role of master modeling in shapingstudentsmorals of SMP Muhammadiyah 10 Surakarta. Beside the purpose of the study is to determine and describe the Role of Exemplary Teachers in moral shaping of students at SMP Muhammadiyah 10 Surakarta. This study uses qualitative research methods, with a background of SMP Muhammadiyah 10 Surakarta. Data collection method used in this study are interviews, observation and documentation. The data,then, are analysed with descriptive qualitative method. The data are collected, described and interpreted in the form of words. Results of research appoint that the role of teachers in the exemplary moral cultivation of students at SMP Muhammadiyah 10 Surakarta, namely:modeling means setting an example, either behavioral, nature, hairdressing, or talk, and so on. Exemplary teachers largely determines the moral cultivation of students at SMP Muhammadiyah 10 Surakarta. Exemplary teachers in a variety of activities will be a mirror for their students. Therefore, a teacher who can emulate learners has a very important position. Teachers used to be discipline, friendly and has morals, will be a good example for their students, and vice versa.